THE STRUCTURE OF SPAWNING POPULATION AND REPRODUCTIVE POTENTIAL OF MULLET IN THE MIDDLE CASPIAN SEA - D. R. Aduyeva; P. S. Taibov (Юг России: экология, развитие, 2014)
As a result of acclimatization of Black Sea mullets of the kind of liza (L.auratus and L.saliens) ichtio industrial herds have been formed. At the same time the nature of migration and adaptive features have changed. Grey mullet sexual puberty in the Caspian Sea happens at the age of 3 or 4. The length and the rate of growth increases. The weight of the Caspian-sea grey mullet is bigger than that of the Black-sea grey mullet.